2013
DOI: 10.4155/fmc.13.58
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibition of Bacterial Two-Component Systems to Combat Antibiotic Resistance and Virulence

Abstract: Infections caused by multidrug-resistant bacteria are a considerable and increasing global problem. The development of new antibiotics is not keeping pace with the rapid evolution of resistance to almost all clinically available drugs, and novel strategies are required to fight bacterial infections. One such strategy is the control of pathogenic behaviors, as opposed to simply killing bacteria. Bacterial two-component system (TCS) signal transduction pathways control many pathogenic bacterial behaviors, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 122 publications
0
66
1
5
Order By: Relevance
“…Much interest has been focused on TCSs as valuable drug targets due to the fact that TCSs are not present in humans and targeting them could reduce virulence (75,76) and antibiotic resistance (76). Inhibitors of a TCS involved in antibiotic resistance could provide effective therapies for treating infections by multidrug-resistant bacteria, in combination with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Much interest has been focused on TCSs as valuable drug targets due to the fact that TCSs are not present in humans and targeting them could reduce virulence (75,76) and antibiotic resistance (76). Inhibitors of a TCS involved in antibiotic resistance could provide effective therapies for treating infections by multidrug-resistant bacteria, in combination with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to tigecycline is mediated by the AdeABC efflux pump, which is controlled by the AdeRS two-component system (TCS) (27)(28)(29)(30)(31). This TCS was recently suggested as a putative drug target for small-molecule intervention to interfere with different antibiotic resistance pathways in A. baumannii (10). In order to evaluate the importance of the transcriptional regulator AdeR in mediating tigecycline resistance in clinical A. baumannii isolates, we customized our gene knockout platform (Fig.…”
Section: Knockout Technology For Genetic Manipulation Of a Baumanniimentioning
confidence: 99%
“…Small molecules that specifically interfere with the transcriptional regulator function may switch off the resistance mechanism. The combination of such inhibitors with a potent antibiotic as an adjuvant drug may provide a new tool to fight infections caused by MDR, XDR, or even PDR pathogens by restoring the efficacy of an approved antibiotic (9,10).…”
mentioning
confidence: 99%
“…TCS regulate the expression of genes that control numerous behaviors including biofi lm formation and maintenance (Gotoh et al 2010 ). Examples of TCS involved in biofi lm regulation include, AgrAC ( S. aureus ) (Gotoh et al 2010 The role of TCS in the control of biofi lm formation and maintenance, and the fact that it has been demonstrated that both the histidine kinase and response regulator are targetable by small molecules makes them attractive targets for the development of anti-biofi lm compounds ( Worthington et al 2013 ). Walkmycin C 50 (Fig.…”
Section: Two-component Systemsmentioning
confidence: 99%